SOCIO-DEMOGRAPHIC CHARACTERISTICS AS DETERMINANTS OF DIFFERENCES IN PERCEPTION OF LOCAL GASTRONOMY - Vuksanović, Nikola; Tešanović, Dragan; Kalenjuk, Bojana; Portić, Milijanko; Knežević, Marija (Economics of Agriculture, 2018)
This study aims to research differences in socio-demographic characteristics of foreign tourists in consumption of local food in the city centres Belgrade and Novi Sad, Republic of Serbia. The research was conducted on a sample of 673 respondents. The results of this study point out the importance of socio-demographic variables in research of local gastronomy as a signifcant component of tourism product. The research included the determining of the impact of the city the tourists stayed at. The differences were examined via two-factor ANOVA analysis of variance. The obtained results indicate that there are differences between age groups, in the level of education, monthly income and countries that foreign tourists come from, whereas there is no difference between genders in relation to the perception of local gastronomy. At the same time, the fndings indicate that there are no differences in the perception of local gastronomy between the cities of Novi Sad and Belgrade. The results confrm previous studies and point out the signifcance of socio-demographic characteristics of foreign tourists in their perception of local gastronomy and adapting it to the visitors, regardless of the city they visited.